Act on clinical trials of medicinal products for human use - scope of regulation and sources of law - Małgorzata Maria Kubacka (Polish Pharmaceutical Society, 2024)
The development of pharmaceutical sciences results in the development of many new medicinal products that require thorough examination of their safety and effectiveness in the course of clinical trials before obtaining marketing authorization. Post-war ethical and legal regulations for conducting clinical trials involving humans have undergone a number of changes over the years. They have one goal in common - to create the most effective protection of the rights and well-being of subjects - clinical trials participants. The aim of the article is to review new regulations of the provisions of the Act of March 9, 2023 on clinical trials of medicinal products for human use and to compare the extra-code criminal provisions of this Act with the repealed criminal provisions of the Pharmaceutical Law. New Act introduced the community solutions contained in Regulation (EU) No. 536/2014 into the Polish legal system. Issues left to the discretion of the Member States were also regulated, including: ethical assessment of applications for authorization for a clinical trial or obtaining informed consent from participants to participate in a clinical trial. A novelty is the establishment of the Clinical Trials Compensation Fund, which was established to ensure payment of compensation for health damage related to a clinical trial for a participant of this trial. In addition, solutions have been introduced for non-commercial clinical trials, which are intended to increase the importance of these trials while supporting non-commercial sponsors and eliminating sponsors - natural persons who do not act as researchers. Unfortunately, the new act does not include provisions enabling earlier access to pharmacotherapy for patients with serious illnesses under the compassionate use procedure. Eligibility for nurses and midwives who have completed higher education in nursing or midwifery has been added - they can now act as principal investigators. Unfortunately, pharmacists have been omitted here. Full digitization of clinical trials and criminal law protection for clinical trial inspections have not been introduced. The extra-code penal provisions contained in the Act were mostly re-written literally from the Pharmaceutical Law Act, after their derogation. Some of them contain repeated semantic shortcomings, as presented in the article. However, this does not change the fact that the legal good of properly conducting clinical trials is adequately protected by these criminal provisions.